2016
DOI: 10.1007/s00404-016-4013-1
|View full text |Cite
|
Sign up to set email alerts
|

Is fetal manipulation during shoulder dystocia management associated with severe maternal and neonatal morbidities?

Abstract: Severe neonatal morbidity does not appear to be associated with FM during SD management, but severe maternal morbidity is associated with FM execution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…McRoberts maneuver and posterior arm rescue (21.2%). Gachon et al reported in their study that episiotomy was more common in patients who performed the maneuver with SD (p < 0.05) [11]. In our study, episiotomy was also more common in patients with SD (p < 0.001).…”
Section: Discussionsupporting
confidence: 65%
“…McRoberts maneuver and posterior arm rescue (21.2%). Gachon et al reported in their study that episiotomy was more common in patients who performed the maneuver with SD (p < 0.05) [11]. In our study, episiotomy was also more common in patients with SD (p < 0.001).…”
Section: Discussionsupporting
confidence: 65%
“…Last resort maneuvers may be more associated with uterine rupture, pubic symphysis diastasis and urinary tract injuries. 36 …”
Section: What Are the Main Maternal And Neonatal Complications Associ...mentioning
confidence: 99%
“…Last resort maneuvers may be more associated with uterine rupture, pubic symphysis diastasis and urinary tract injuries. (36) Neonatal injuries aff ect 5% of cases of shoulder dystocia. They can occur even when treatment is properly instituted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation